Cytotoxic T lymphocytes as a potential brake of keratinocyte proliferation in psoriasis. (February 2016) - Vičić, Marijana; Peternel, Sandra; Simonić, Edita; Sotošek-Tokmadžić, Vlatka; Massari, Dražen; Brajac, Ines; Kaštelan, Marija; Prpić-Massari, Larisa
Abstract: Psoriasis is a chronic papulosquamous skin disease, histologically characterized by epidermal hyperproliferation and dermal infiltration of inflammatory cells. The majority of T lymphocytes infiltrating dermis are CD4+ T lymphocytes secreting type 1 and type 17 cytokines. These cytokines are responsible for triggering keratinocyte proliferation as well as chemokine secretion and subsequent migration of other inflammatory cells in the skin. Contrarily, lymphocytes that accumulate in epidermis are mainly CD8+ T lymphocytes. According to the recent findings, these cells can also secrete type 1 and type 17 cytokines. However, it is demonstrated so far that epidermal CD8+ T lymphocytes contain higher amounts of cytolytic molecules, such as perforin, granzyme B and granulysin whose role in psoriasis pathogenesis is still unknown. Therefore, in this article we hypothesize the active involvement of cell mediated cytotoxicity in killing the proliferating keratinocytes as a mechanism of potential self-defense and possible brake in psoriatic plaque formation, maintaining skin homeostasis.